Chemical Weed Control in Direct Seeded Rice: The Evaluation of Selected Herbicides for Phytotoxicity to the Rice Plant - Man, Azmi; Lim, E. S. (1986)
The phytotoxic effect of 2,4-D amine, 2,4-DIBE-butachlor; butachlor, benthiocarb and molinate on rice plants were assessed. Applications of the herbicides at different time resulted in severe phytotoxicity when applied before seeding. Early postemergent applications were also generally phytotoxic, adversely affecting plant growth and grain yield. Late applications 8 to 10 weeks after seeding were least injurious. Among the herbicides, molinate was the least phytotoxic.